2004
DOI: 10.2337/diacare.27.2.461
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a Safe and Effective Insulin Infusion Protocol in a Medical Intensive Care Unit

Abstract: OBJECTIVE -In a recent randomized controlled trial, lowering blood glucose levels to 80 -110 mg/dl improved clinical outcomes in critically ill patients. In that study, the insulin infusion protocol (IIP) used to normalize blood glucose levels provided valuable guidelines for adjusting insulin therapy. In our hands, however, ongoing expert supervision was required to effectively manage the insulin infusions. This work describes our early experience with a safe, effective, nurse-implemented IIP that provides de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
273
2
16

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 427 publications
(298 citation statements)
references
References 22 publications
7
273
2
16
Order By: Relevance
“…[16][17][18] Though intravenous insulin use was associated with better overall glucose control in our study; only about 50% of ICU patients received it on measurement day 1. A recent prospective randomized clinical trial demonstrated superior glycemic control in non-critically ill hospitalized patients with type 2 diabetes with basal/bolus insulin therapy compared to sliding scale insulin alone.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…[16][17][18] Though intravenous insulin use was associated with better overall glucose control in our study; only about 50% of ICU patients received it on measurement day 1. A recent prospective randomized clinical trial demonstrated superior glycemic control in non-critically ill hospitalized patients with type 2 diabetes with basal/bolus insulin therapy compared to sliding scale insulin alone.…”
Section: Discussionmentioning
confidence: 49%
“…15 There is now emerging consensus that use of continuous insulin infusion given through a standardized protocol is the standard of care to control hyperglycemia in critically ill patients. [16][17][18] Likewise, use of specific hospital insulin regimens that include basal and short-acting insulin with appropriate bedside glucose monitoring and avoiding use of ''sliding scale'' short-acting insulin alone has become recognized as the most effective approach for glucose management in hospitalized patients not requiring intravenous insulin. 4,[19][20][21] The University HealthSystem Consortium (UHC) is an alliance of 97 academic health centers and 153 of their associated hospitals that conducts benchmarking studies on clinical and operational topics with member academic medical centers and develops new programs to improve quality of care, patient safety, and operational, clinical, and financial performance.…”
mentioning
confidence: 99%
“…Insulin can be started either as insulin and glucose infused separately or glucose insulin potassium (GIK) combined solution. While a number of validated and effective protocols for insulin infusion are in use [6,20,27,29], we suggest the following as a simplified method.…”
Section: Regimen For Continuous Insulin Infusionmentioning
confidence: 99%
“…Alternatively, a supplemental subcutaneous bolus of regular insulin may be administered if patient is haemodynarnically stable. [29]: Prepare insulin drip by adding 50 units of human regular insulin to 500 ml of normal saline. Infusion set should be flushed with 30 ml of solution to saturate binding sites in the tubing.…”
Section: Regimen For Continuous Insulin Infusionmentioning
confidence: 99%
“…45-50, GlucoCare (Pronia Medical Systems, Louisville, KY), EndoTool (Hospira, Lake Forest, IL), and GlucoStabilizer (Alere Informatics Solutions, formerly Medical Automation Systems, Charlottesville, VA) are other industrial SG protocols with documented efficacy. [51][52][53][54]46 The newest algorithms fall into the category of model predictive controls (MPCs). By incorporating dextrose administration, insulin sensitivity, age, diabetes diagnosis, and several other patient-specific parameters, these protocols attempt to predict a patient's response to hyperglycemia and IIT.…”
Section: Introductionmentioning
confidence: 99%